#### Example 7.92.

Solve the equation \(~~\displaystyle{\frac{60}{15-x}=9}\)

## Solution.

We multiply both sides of the equation by \(\alert{15 - x}\) to obtain

\begin{align*}
\alert{(15 - x)}\frac{60}{15-x}\amp =9\alert{(15 - x)}\\
60 \amp = 9(15 - x)\amp\amp \blert{\text{Apply the distributive law.}}
\end{align*}

From here we can proceed as usual.

\begin{align*}
60 \amp = 135 - 9x\amp\amp \blert{\text{Subtract 135 from both sides.}}\\
-75 \amp = -9x\amp\amp \blert{\text{Divide by }-9.}\\
8.\overline{3} \amp = x
\end{align*}

The windspeed was \(8.\overline{3}\text{,}\) or \(8\frac{1}{3}\) miles per hour.